Abnormality and Stigmatization in Irvine Welsh's Trainspotting - Gutiérrez Sibaja, Alfonso 1985-
The article proposes a reading of Irvine Welsh's Trainspotting that parts from previous criticism that mostly concerned itself with debating asupposed glamorization of heroin abuse. Instead, this article focuses on the discursive mechanisms that classify the novel's characters as abnormal subjects with a created need to be disciplined and normalized. Specifically, it addresses Mark Renton's classification as abnormal in terms of ideology and drug addiction and how such labeling is related to stigmatization. Theoretical considerations regarding abnormality, stigmatization and the psychiatric discourse from the works of Michel Foucault, Erwin Goffman and Thomas Szasz are incorporated to the discussion of Mark Renton's mechanomorphist construction and its violent implications.